Subsurface Flow and Dissolve Organic Carbon (DOC) Pathways in a Forested Headwater Catchment - K SUBAGYONO; T TANAKA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2010)
Soils under forested catchment are generally rich in organic matter, yet the role of organic soil layers in flow governing hydrochemical processes has rarely studied. Understanding the subsurface process and the role of rich organic matter at A horizon has been studied in Kawakami forestedheadwater catchment in Nagano prefecture, Central Japan from August 2000 to August 2001. The catchment is dominated by Inceptisols with 0.2-0.3 m of peat covering the soil in the riparian zone. Oak (Quercus mongolica Fisch) and bamboo grass (Sasa nipponica) are dominant vegetation in the catchment. The study is aimed to elucidate (a) can dissolved organic carbon (DOC) pathways be an indicator for tracing subsurface flow in a forested headwater catchment?, and (b) how does flushing effect the dynamic of DOC concentration?. Hydrometric and dynamic behavior of DOC as well as its variation were recorded in atransect across hillslope and riparian zone. The results showed that DOC has a specific trend across the riparian and the hillslope areas. During baseflow condition, DOC decreased with depth and away from the stream channel. The change in DOC concentration was clearly controlled by the flow pattern. In the near surface riparian, where the lateral flow was relatively steady and sustained in the direction of the stream, may facilitate theflushing high concentration of DOC. In the riparian zone, DOC concentration at the surface horizons of 0.3 and 0.6 m depth tend to decrease near the peak storm, which attributed to flushing of its high concentration. Under the three components mixing model involving the near surface riparian, the deep riparian groundwater, and the hillslope soil water contributing to stormrunoff, DOC was in concave clockwise rotation with positive trend correspond to Evans and Davies (1998) case in which CNSR > CHSW > CDRG (C2 model). This was well confirmed with (a) the hydrochemistry data in which the concentration of DOC was higher in the near surface riparian zones, and (b) the hydrometric data in which the highest contributor to the storm runoff was the near surface riparian. The C2 model is the highest level offlushing in the sequence proposed by Evans and Davies (1998) confirming the highest control of the near surface riparian zone on the stream DOC concentrations.